2020
DOI: 10.1002/hbm.25212
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial and subcortical volumes in adolescents with early‐onset psychosis: A multisite mega‐analysis from the ENIGMA consortium

Abstract: Early-onset psychosis disorders are serious mental disorders arising before the age of 18 years. Here, we investigate the largest neuroimaging dataset, to date, of patients with early-onset psychosis and healthy controls for differences in intracranial and subcortical brain volumes. The sample included 263 patients with early-onset psycho-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…Given that intracranial brain volume stabilizes and is maintained in early-to mid-adolescence 72 , it is not illogical to assert that schizophrenia is a neurodevelopmental disorder. In support of this hypothesis, several reports have demonstrated distinct deficits in hippocampal volume in young patients in mid-to-late adolescence following a first psychotic episode 73,74 . Unfortunately, during this critical juncture of adolescent neurodevelopment, when intracranial brain substructures are still undergoing maturation and development, hippocampal volume does not seem to be restored by antipsychotic drug treatment 74 .…”
Section: Neurogenesis and Psychosismentioning
confidence: 75%
See 2 more Smart Citations
“…Given that intracranial brain volume stabilizes and is maintained in early-to mid-adolescence 72 , it is not illogical to assert that schizophrenia is a neurodevelopmental disorder. In support of this hypothesis, several reports have demonstrated distinct deficits in hippocampal volume in young patients in mid-to-late adolescence following a first psychotic episode 73,74 . Unfortunately, during this critical juncture of adolescent neurodevelopment, when intracranial brain substructures are still undergoing maturation and development, hippocampal volume does not seem to be restored by antipsychotic drug treatment 74 .…”
Section: Neurogenesis and Psychosismentioning
confidence: 75%
“…In support of this hypothesis, several reports have demonstrated distinct deficits in hippocampal volume in young patients in mid-to-late adolescence following a first psychotic episode 73,74 . Unfortunately, during this critical juncture of adolescent neurodevelopment, when intracranial brain substructures are still undergoing maturation and development, hippocampal volume does not seem to be restored by antipsychotic drug treatment 74 . While the average age of onset of the initial psychosis episode occurs after early adolescence in females (early twenties to early thirties) and males (late teens to late twenties), clinical epidemiological investigations have revealed that psychosis manifestations are often preceded by poor academic performance 75,76 .…”
Section: Neurogenesis and Psychosismentioning
confidence: 75%
See 1 more Smart Citation
“…Building on earlier work that suggested a "compensatory" effect in unaffected first-degree relatives of patients with bipolar disorder, de Zwarte et al ( 2020) note the modulating effects of cognitive performance and educational attainment on brain abnormalities in those at familial high risk for bipolar disorder and schizophrenia. A related paper by Gurholt et al (2020) examines intracranial and subcortical volumes in adolescents with early-onset psychosis-a severe and often progressive form of the disorder. Recently, ENIGMA working groups have been created to study various conditions on the schizophrenia spectrum-including the first large-scale international studies of schizotypy (Kirschner et al, 2021).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…To date, there is insufficient knowledge on how brain maturation is linked to the emergence of psychosis and neuroimaging studies on these co-occurring processes are important. While a few magnetic resonance imaging (MRI) studies in EOP report grey matter brain abnormalities (11)(12)(13)(14), including a recent multisite mega-analysis from the ENIGMA EOP Working Group (15), less is known about putative white matter alterations. This is a critical research gap, as understanding how white matter microstructure is affected in EOP may provide important insights into the pathophysiology of psychotic disorders during adolescent brain development.…”
Section: Introductionmentioning
confidence: 99%